Improving Students' Mathematical Problem-Solving Skills Through Interactive Learning Approaches at SMP Negeri 23 Medan - Agus Selamat Telaumbanua (Gunung Djati Conference Series, 2026)
This study aims to analyze the effect of an interactive learning approach on the mathematical problem-solving abilities of students at SMP Negeri 23 Medan. The study used a quasi-experimental method with a Pretest-Posttest Control Group Design. The sample consisted of 70 students divided into an experimental class and a control class, each with 35 students. The research instrument was a mathematical problem-solving ability test administered before and after the treatment. Data were analyzed using descriptive statistics and N-Gain calculations. The results showed that the average pretest score of the experimental class increased from 58.34 to 84.75 on the posttest, with an N-Gain of 0.72 (high category). Meanwhile, the control class experienced an increase from 57.91 to 72.48 with an N-Gain of 0.35 (moderate category). The results showed that the interactive learning approach was more effective than conventional learning in improving students' mathematical problem-solving abilities. These findings indicate that active student involvement through discussion, collaboration, concept exploration, and the use of interactive media can improve conceptual understanding and critical thinking skills in solving mathematical problems.